Effect of sustainable agricultural intensification practices on cost efficiency of smallholder crop farmers in southeastern Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
This study investigated the effect of sustainable agricultural intensification practices on the cost efficiency of smallholder crop farmers in southeastern Nigeria. A multi-stage random sampling technique was employed in selecting 360 respondents for the study. Simple descriptive tools (mean, frequencies, and percentages) as well as inferential statistics (stochastic frontier cost function) were employed in achieving the objectives. The maximum likelihood estimates of the stochastic cost function revealed that the explanatory variables; farm size, labor costs, fertilizer expenses, and capital investments were significantly and positively related to cost efficiency in the study area, while farming experience (p
Keywords: Cost function; Farmers; Smallholder; Sustainable intensification; Technology adoption